Effects of the fresh and dried housefly (Musca domestica) larvae in the diets of Nile tilapia Oreochromis niloticus (Linnaeus, 1758): growth, feed utilization efficiency, body composition and biological indices - ALOFA, Cayen Sédro; ABOU, YOUSSOUF; OLODO, Isabella; CHABI KPERA, Mouhamed (My University, 2023)
A 56-day feeding trial was undertaken to assess the effects of housefly maggots (HM) forms (dried and fresh) as protein sources on growth, feed efficiency, and body indices of Oreochromis niloticus fingerlings. A control diet (T0) contained 300 g/kg of fishmeal (without HM). Two practical diets with the same formula were prepared with dried HM (T1) and fresh HM (T2) where 66 % of the fishmeal was replaced. Diets were fed to triplicate groups of tilapia (mean initial weight: 10.26 ±0.12 g). There was no difference in survival, condition factor, feed conversion ratio, and protein efficiency ratio. Fish fed diets T0 and T1 had significantly increased (P < 0.05) mean final weight (50.25 ±1.39 - 52.24 ±1.03 g), specific growth rate (2.84 ±0.03 - 2.88 ±0.03 %/day) and weight gain (389.70 ±7.63 - 402.78 ±8.16 %) compared to T2 diet ones (46.30 ±2.03 g; 2.67 ±0.07 %/day and 356.70 ±7.76 % respectively). Viscerosomatic and hepatosomatic index in fish fed T1 and T2 diets were significantly higher than those fed T0. The present findings indicate that the dried form of housefly maggot has given the best results in terms of growth compared to the live form. However, housefly forms did not affect feed efficiency parameters.
Keywords: Maggot meal; Fresh maggot; Forms; Carcass composition; Tilapia